Enhanced bioturbation on the down‐drift flank of a Turonian asymmetrical delta: Implications for seaway circulation, river nutrients and facies models. Issue 7 (13th August 2015) - Korus, Jesse T.; Fielding, Christopher R.
Abstract: Extant models predict delta front environments down‐drift of river mouths as unfavourable for organisms because of the physico‐chemical stresses caused by sediment and fresh water influx. This study, however, finds evidence for near‐optimal living conditions down‐drift of contemporaneous mouth bars and distributary channels, as well as at the tops of abandoned lobes, in part of the asymmetrical 'Notom Delta' complex of the Ferron Sandstone (Turonian, south‐eastern Utah, USA). Presented herein is a sedimentological and ichnological model using thirty‐two detailed measured sections along a 16 km transect through two continuously exposed, ca 10 m thick allomembers containing delta front, mouth bar and distributary channel facies. Azimuths from sedimentary structures show south‐eastward deflection of near‐shore palaeocurrents relative to the inferred north–south shoreline, as well as minor reversal of flow. Two end‐member trace fossil suites are recognized in delta front sandstones: (i) a stressed suite of low abundance, low diversity, diminutive traces reflecting mobile deposit feeding, resting and locomotion behaviours; and (ii) a comparatively unstressed, high abundance, moderate diversity suite with a regular, heterogeneous distribution of deep, vertical or U‐shaped suspension‐feeding burrows which, in places, thoroughly homogenize the sandstones. The down‐drift side of the delta was colonized by suspension feeders during seasonal reversal of the seaway gyre when mud plumes were swept northward or when river‐derived nutrients were sufficiently concentrated relative to fresh water and sediment input. During normal seaway circulation, very high sedimentation rates and mud‐laden, wave‐dampened waters down‐drift of the river mouths heightened the preservation potential of the pervasively bioturbated facies. Up‐drift of the river mouths, these bioturbated facies were either not preserved or not developed until the lobe was abandoned. This alternative model for delta planform asymmetry contributes to the refinement of facies models for deltaic systems and provides a framework for predicting the distribution of bioturbation‐enhanced porosity and permeability in lobe‐deflected deltas.